2012
DOI: 10.3389/fnmol.2012.00030
|View full text |Cite
|
Sign up to set email alerts
|

Stressing hematopoiesis and immunity: an acetylcholinesterase window into nervous and immune system interactions

Abstract: Hematopoietic stem cells (HSCs) differentiate and generate all blood cell lineages while maintaining self-renewal ability throughout life. Systemic responses to stressful insults, either psychological or physical exert both stimulating and down-regulating effects on these dynamic members of the immune system. Stress-facilitated division and re-oriented differentiation of progenitor cells modifies hematopoietic cell type composition, while enhancing cytokine production and promoting inflammation. Inversely, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…AChE is known to be secreted by other parasites [22,23], including the saliva of blood feeding insects [24,25]. AChE is known to be involved in vertebrate immune function [26,27], and secretion of AChE in tick saliva may be involved in promoting feeding by hydrolyzing platelet activating factor [24], or inhibiting infiltration of lymphocytes [28] and wound healing [29] by reducing local tissue concentration of acetylcholine. In addition, salivary AChE may provide modulation of the host immune response [30][31][32], or protection of the tick from effects of acetylcholine contained in the large volume of ingested blood from the host.…”
Section: Ticksmentioning
confidence: 99%
See 1 more Smart Citation
“…AChE is known to be secreted by other parasites [22,23], including the saliva of blood feeding insects [24,25]. AChE is known to be involved in vertebrate immune function [26,27], and secretion of AChE in tick saliva may be involved in promoting feeding by hydrolyzing platelet activating factor [24], or inhibiting infiltration of lymphocytes [28] and wound healing [29] by reducing local tissue concentration of acetylcholine. In addition, salivary AChE may provide modulation of the host immune response [30][31][32], or protection of the tick from effects of acetylcholine contained in the large volume of ingested blood from the host.…”
Section: Ticksmentioning
confidence: 99%
“…AChE is known to be involved in vertebrate immune function [26,27], and secretion of AChE in tick saliva may be involved in promoting feeding by hydrolyzing platelet activating factor [24], or inhibiting infiltration of lymphocytes [28] and wound healing [29] by reducing local tissue concentration of acetylcholine. In addition, salivary AChE may provide modulation of the host immune response [30][31][32], or protection of the tick from effects of acetylcholine contained in the large volume of ingested blood from the host. The phylogram depicting amino acid sequences purportedly encoded by AChE genes of I. scapularis and confirmed AChEs of R. microplus shown in Fig.…”
Section: Ticksmentioning
confidence: 99%
“…This can affect the function and intracellular distribution of proteins, which is important during cellular differentiation and development, for physiological functions, and in pathological states (Eizirik et al, 2012;Gilboa-Geffen et al, 2012). In previous studies we showed that immune-related genes play important roles in bovine mastitis via alternative splicing (Huang et al, 2011;Hou et al, 2012;Li et al, 2013;Wang et al, 2014;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism involves the interaction of AChE-S with the anti-apoptotic C-terminal binding protein (CtBP), thus reducing T lymphopoiesis, in contrast to the effect of AChE-R, which upregulates haematopoiesis (Gilboa-Geffen et al, 2012).…”
Section: Supporting Publications 2016: En-955 126mentioning
confidence: 99%
“…These events result in over-production of AChE and replacement of the synaptic AChE (AChE-S, the major stable AChE splice variant) by the less stable read through (AChE-R) variant (Gilboa-Geffen et al, 2012), which displays morphogenic functions in multiple embryonic and tumour cells (Grisaru et al, 2006). Under stress responses, blood AChE-R undergoes C-terminal cleavage to release the C-…”
Section: Role Of Acetylcholinesterase In Leukaemogenesismentioning
confidence: 99%